2013
DOI: 10.1590/s0034-76122013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de legitimidade de Suchman evidenciadas nos relatórios da administração de empresas públicas do setor elétrico

Abstract: Este estudo objetiva identificar as estratégias de legitimidade da tipologia de Suchman (1995) evidenciadas nos relatórios da administração de empresas públicas estaduais brasileiras de capital aberto do setor de energia elétrica. Investigação com abordagem qualitativa foi realizada por meio de pesquisa documental, com análise de conteúdo. Os resultados da pesquisa revelam a presença das quatro categorias de legitimidade, e 556 citações evidenciaram essas estratégias de legitimidade. A estratégia com maior des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
(34 reference statements)
0
11
0
11
Order By: Relevance
“…In the Brazilian case, companies listed in the CSI are committed to sustainability and CSR, and are considered references for socially responsible investments (Dani et al, 2013). Beuren et al (2013) observed that Administration Reports (ARs) present a greater volume of environmental disclosure and that companies did not disclose environmental provisions and liabilities and accounting practices involving environmental items. Nossa (2002) argued that there are divergences in disclosure between companies in relation to their size, the country where they are located and differences between the financial report and the specific environmental report.…”
Section: Contemporary Studies On Corporate Governance Corporate Socimentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brazilian case, companies listed in the CSI are committed to sustainability and CSR, and are considered references for socially responsible investments (Dani et al, 2013). Beuren et al (2013) observed that Administration Reports (ARs) present a greater volume of environmental disclosure and that companies did not disclose environmental provisions and liabilities and accounting practices involving environmental items. Nossa (2002) argued that there are divergences in disclosure between companies in relation to their size, the country where they are located and differences between the financial report and the specific environmental report.…”
Section: Contemporary Studies On Corporate Governance Corporate Socimentioning
confidence: 99%
“…This contributes to the reduction of the asymmetry in investor information (cf. Lopatta et al, 2016) -desirable from the point of view of the shareholders and other stakeholders, as pointed out by Beuren et al (2013), and is related, in the view of Frias-Aceituno et al (2014), to agency and signalling theories. Furthermore, voluntary financial disclosure can be conditioned to CG practices and marketing strategies, or also taken into consideration and dealt with to demonstrate greater transparency in the organization, or better levels of CSR, being related, according to González Esteban (2007), to stakeholder theory, which stresses the importance of the theme and equally justifies the execution of the research.…”
Section: Introductionmentioning
confidence: 99%
“…Os impactos socioambientais das empresas têm sido alvo de estudos de diversas ciências, inclusive a contábil, que estuda o modo como às organizações divulgam essa temática informacional em seus demonstrativos contábeis. Uma das teorias mais utilizadas para embasar a divulgação de informações ambientais nos relatórios financeiros é a Teoria da Legitimidade, cuja base argumenta que as entidades procuram divulgar informações relacionadas com a sustentabilidade a fim de passar para a sociedade uma impressão de boas práticas (BEUREN et al, 2013).…”
Section: Introductionunclassified
“…Além disso, ressalta-se a amplitude do período de análise, possibilitada pela coleta de dados realizada na Biblioteca Nacional do Rio de Janeiro. Desse modo, o presente trabalho diferencia-se das pesquisas nacionais sobre o tema (Beuren, Gubiani, & Soares, 2013;Beuren, Hein, & Boff, 2011;Fank & Beuren, 2010) que, por utilizarem apenas RAs disponibilizados na base de dados da BM&FBOVESPA, limitaram suas análises aos anos posteriores a 1997. Por fim, no que tange à contribuição prática, a análise poderá propiciar aos gestores reflexões sobre a importância de estarem atentos às mudanças sociais para garantir longevidade à organização.…”
Section: Introductionunclassified